Effects of liquid natural rubber (LNR) on the mechanical properties of LNR toughened epoxy composite - Lee, Yip Seng; Sahrim Hj. Ahmad, Rozaidi Rasid,; Se Yong Eh Noum,; Yew, Chin Hock; Mou’ad A. Tarawneh, (Universiti Kebangsaan Malaysia, 2011)
The effects of liquid natural rubber (LNR) on the morphology and mechanical properties of rubber modified epoxy were investigated. Epoxy composites were prepared in four different compositions of LNR (3, 5, 7 and 9phr) by using twin screw extruder. The samples for tensile, fracture toughness and impact tests were prepared according to ASTM D 638, D 5045 and D 256. The elastomeric nature of rubber can act as energy dissipating centre to cause the ductile fracture for the rubber modified epoxy. They was an obvious increment of fracture toughness where maximum value was observed with 3 phr LNR. A clear increment of impact strength at 3 phr LNR was observed, followed by a small increment at 5 phr and no further increment at 7 and 9 phr LNR. The tensile strength showed a similar trend with impact strength and Young’s modulus. SEM micrographs showed an increment of rubber particle size when the amount of LNR was increased and caused the mechanical properties to drop.